Pengembangan Bahan Ajar Elektronik pada Materi Akhlak Mata Pelajaran Pendidikan Agama Islam - Kafi, Muhammad Kafnun (Epistemic: Jurnal Ilmiah Pendidikan, 2023)
The development of electronic teaching materials for Ahlak (moral education) in Islamic Religious Education (PAI) is essential to facilitate the understanding of Ahlak concepts in a more interactive and engaging manner for students. This study aims to design and develop effective electronic teaching materials by utilizing information technology to enrich the learning process. The research methodology used is a literature study, which includes a critical analysis of literature related to the development of electronic teaching materials and Ahlak theories. The findings indicate that the use of electronic teaching materials can enhance students' engagement and understanding of Ahlak by providing more dynamic and interactive content. This development allows students to learn at their own pace, access learning materials from various devices, and gain a deeper understanding of moral and ethical values. The implications of this research highlight the need for integrating technology into moral education and propose innovative approaches in designing relevant and engaging teaching materials. The study also identifies several limitations, such as technology accessibility and challenges in measuring the effectiveness of learning. Future development prospects include the adoption of similar approaches by other educational institutions and regular evaluations to ensure the effectiveness of electronic teaching materials.